A transparent electromagnetic-shielding film based on one-dimensional metal–dielectric periodic structures - 赵亚丽;马富花;李旭峰;马江将;贾琨;魏学红 (Chinese physics B, 2018)
In this study, we designed and fabricated optical materials consisting of alternating ITO and Ag layers. This approach is considered to be a promising way to obtain a light-weight, ultrathin and transparent shielding medium, which not only transmits visible light but also inhibits the transmission of microwaves, despite the fact that the total thickness of the Ag film is much larger than the skin depth in the visible range and less than that in the microwave region. Theoretical results suggest that a high dielectric/metal thickness ratio can enhance the broadband and improve the transmittance in the optical range. Accordingly, the central wavelength was found to be red-shifted with increasing dielectric/metal thickness ratio. A physical mechanism behind the controlling transmission of visible light is also proposed. Meanwhile, the electromagnetic shielding effectiveness of the prepared structures was found to exceed 40 dB in the range from 0.1 GHz to 18 GHz, even reaching up to 70 dB at 0.1 GHz, which is far higher than that of a single ITO film of the same thickness.